Germanium in donbas coal as a strategic element - Kozii, Ye. S.; Козій, Є. С. (Державний університет «Житомирська політехніка», 2025)
Currently, coal deposits in Ukraine that are characterized by germanium metal content are not being fully and comprehensively exploited, the reserves of this strategic metal are written off in accordance with coal extraction. To relaunch the domestic germanium production complex, it is critically necessary to conduct continuous monitoring of the germanium content in commercial coal and in the coal seams under development, as well as to modernize and restore the units at coke -chemical plants used to obtain germanium concentrate, employing advanced resource-saving technologies for processing coal tar wastewater.